2007
DOI: 10.1111/j.1553-2712.2007.tb02352.x
|View full text |Cite
|
Sign up to set email alerts
|

The Need for Emergency Medicine Resident Training in Informed Consent for Procedures

Abstract: Few residents have had formal training in informed consent, and there is wide variability in the perception of which procedures require informed consent. Residents are not confident in their knowledge of all risks and benefits of common procedures, and comfort levels in obtaining informed consent are low. Residents can benefit from additional resources that provide standardized information and formal training on the issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 11 publications
0
12
0
1
Order By: Relevance
“…The markedly lower consent rates when additional and specific information was given regarding how the trainee will be participating highlights the need to carefully evaluate not only the results of this and other studies but also the exact wording of the questions and response choices. Although this and other studies 11,17 have found decreased consent rates when additional information regarding trainee participation is provided, it is unclear whether these effects could be counterbalanced by educating patients regarding the positive aspects of care in a teaching setting. Our results suggest that patient understanding and perceptions may significantly affect their attitude toward surgical education.…”
Section: Commentmentioning
confidence: 57%
See 1 more Smart Citation
“…The markedly lower consent rates when additional and specific information was given regarding how the trainee will be participating highlights the need to carefully evaluate not only the results of this and other studies but also the exact wording of the questions and response choices. Although this and other studies 11,17 have found decreased consent rates when additional information regarding trainee participation is provided, it is unclear whether these effects could be counterbalanced by educating patients regarding the positive aspects of care in a teaching setting. Our results suggest that patient understanding and perceptions may significantly affect their attitude toward surgical education.…”
Section: Commentmentioning
confidence: 57%
“…Trainees themselves have frequently not volunteered this information, particularly in the setting of obtaining consent for an invasive procedure. 11,14 In a detailed interview of 30 attending surgeons in an academic hospital, Knifed et al 5 found that most (83%) did not volunteer information regarding trainee participation during the informed consent process. They also demonstrated the willingness of attending surgeons to allow active trainee participation, with 87% allowing residents to operate while the attending surgeon was not adequately dressed and washed for surgery but was present and 77% allowing residents to operate when their attending surgeon was not present in the operating room.…”
Section: Commentmentioning
confidence: 99%
“…Residents performed worse compared to surgeons in Ireland, Germany, UK and USA [23-25,28]. They do not feel confident due to a lack of training [5,13,23,24,26,29], and up to 60% of residents in the USA claimed that they never received any feedback on these issues during their residency [29,30]. In recent years, informed consent was topic of debate in the USA and the UK and improvements in care followed.…”
Section: Discussionmentioning
confidence: 99%
“…The junior doctors particularly the residents are usually the front line healthcare providers in developing as well as developed countries, however they are often not well versed with the process of SIC, and hence err by not giving information about the potential complications of the planned procedures or alternative treatments and mostly provide only information on the benefits of particular surgical interventions (13)(14)(15). Lack of practical experience as well as deficient training on part of the residents in the critical area of doctor-patient communication are the possible explanations for their poor performance in the process of SIC (7,9,(16)(17)(18)(19)(20). Our findings of the study constitute a compelling evidence for educating residents in this particular area of doctor-patient communication in future.…”
Section: Discussionmentioning
confidence: 99%